IMPLEMENTASI APLIKASI STOK BARANG PERANGKAT JARINGAN BERBASIS WEB DI PT ZATHCO - Inneke putri; Dwi prapita sari; Mhd ikhsan rifki (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The system currently used experiences problems in handling recipient and delivery data, customer data, and inventory data which are recorded on paper and only copied by the admin to the company computer. These problems can result in product calculation errors, problems in recording and reporting product recipients and deliveries, and in several months the product in and out can reach the target. There are often differences in inventory. This is caused by a helper or admin error. The warehouse department is recording, receiving and sending products. In addition, the accumulation of large numbers of files can make it difficult to find the product data you need, and searching files can take time and interfere with other tasks. The aim of this research is to develop an inventory management application that can manage recipient or delivery data, inventory data, and delivery data using visual modeling used in building object-oriented systems and waterfall system development methods. This is about developing a website that is created to simplify incoming goods data and outgoing goods data so that it can help business processes in the company.